(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In order to radically change the exercises in physical education classes, as well as to increase the effectiveness of the lesson, we used the rotational exercise method in physical education classes. The main goal was to develop the ability of students to be quick.